Ivanka Trump businesswoman and first daughter - Hoffman, Megan Mills (New York Cavendish Square Publishing, 2018)
Ivanka Trump is a woman who rose to fame not only through her family name but also for her successes in the fashion, entertainment, and business worlds. This is her story, from model to influential First Daughter. Complete with vivid photographs, detailed chronologies, and sidebars, this book offers insight into one of the most talked-about women and families in recent times.
Introduction to Ivanka Trump -- Early successes -- Entry into the public eye -- Main contributions -- Activism -- Recognition and future plans.
Includes bibliographical references and index.
105822
Keywords: Trump, Ivanka -- 1981-; Children of presidents -- United States -- Biography -- Juvenile literature; Women -- Biography; United States; Biography; Juvenile works